Dysregulation of methionine metabolism in multiple sclerosis. (January 2018) - Singhal, N.K.; Freeman, E.; Arning, E.; Wasek, B.; Clements, R.; Sheppard, C.; Blake, P.; Bottiglieri, T.; McDonough, J.
Abstract: We report a significant reduction in plasma methionine concentrations in relapse remitting multiple sclerosis (MS) patients compared to controls. In vivo studies demonstrate that changes in peripheral methionine levels in mice can regulate histone H3 methylation and expression of DNA methyltransferase 3A (DNMT3A) centrally, in the cerebral cortex. Therefore, we propose that decreases in circulating methionine represent one of the earliest manifestations of dysregulated methionine metabolism in MS with potential impacts on both histone H3 and DNA methylation in the central nervous system. Highlights: Methionine is significantly reduced in blood plasma of MS patients at relapse remitting stages. Levels of H3K4me3 are reduced in postmortem MS cortical samples. Peripheral methionine administration increases SAM and methionine in mouse brain. Methionine supplementation increases levels of H3K4me3 and DNMT3A in mouse brain. Dietary supplementation that supports methionine metabolism may be helpful in multiple sclerosis.